2019
DOI: 10.1111/irv.12679
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial transmission of influenza: A retrospective cross‐sectional study using next generation sequencing at a hospital in England (2012‐2014)

Abstract: BackgroundThe extent of transmission of influenza in hospital settings is poorly understood. Next generation sequencing may improve this by providing information on the genetic relatedness of viral strains.ObjectivesWe aimed to apply next generation sequencing to describe transmission in hospital and compare with methods based on routinely‐collected data.MethodsAll influenza samples taken through routine care from patients at University College London Hospitals NHS Foundation Trust (September 2012 to March 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…For influenza, WGS offer superior resolution for molecular epidemiology compared to single segment analysis [193] . In a recent report from U.K, WGS data confirmed nosocomial transmission for approximately 16% of cases [194] . Equally to the impact of DNA-techniques on criminology, outbreak investigations need to include and integrate laboratory data with epidemiologic data to obtain full value [195,196] .…”
Section: Outbreak Analysismentioning
confidence: 93%
“…For influenza, WGS offer superior resolution for molecular epidemiology compared to single segment analysis [193] . In a recent report from U.K, WGS data confirmed nosocomial transmission for approximately 16% of cases [194] . Equally to the impact of DNA-techniques on criminology, outbreak investigations need to include and integrate laboratory data with epidemiologic data to obtain full value [195,196] .…”
Section: Outbreak Analysismentioning
confidence: 93%
“…In 2017/8 this was estimated to be 15 % of influenza cases diagnosed during the influenza season. A recent study using phylogenetic analysis of influenza isolates demonstrated genetic clustering in 15.8 % of hospital influenza cases indicating nosocomial acquisition [ 19 ]. Nosocomial acquisition of influenza has knock-on effects in terms of morbidity and delays to discharge, the financial impact of which has not been clarified and further studies are needed to understand the economic effects of these aspects in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Algunas soluciones convencionales como limpiadores de aires se encuentran bajo evaluación para probar su capacidad en escenarios relevantes [4], sin embargo, esos sistemas no han sido probados en entornos tales como hospitales, con carga viral confirmada de SARS-CoV2. La diseminación de patógenos infecciosos en hospitales puede ser significativa y, en varios escenarios, el requisito es contar con un ambiente libre de patógenos (por ejemplo, en quirófanos) no sólo para protección de pacientes sino también del personal del hospital [5]. Se ha demostrado que la generación de iones negativos puede reducir la transmisión de enfermedades debido a patógenos como virus [6] y bacterias [7].…”
Section: Planteamiento Del Problemaunclassified